(untitled) (Journal of the College of Basic Education, 2025)
The study aimed to identify the impact of climatic elements on land transportation in the periods in which climatic risks occur during the year, and to identify the most important transportation networks and the changes that occurred in them in the future. The study followed the following approaches: historical, regional, descriptive, statistical and analytical. Interview, observation, and questionnaire were used as tools for the study. The study also relied on secondary sources represented in books, periodicals, university theses, reports and records. Data were analyzed using Statistical Package for the Social Sciences (SPSS) . The study reached results, the most important of which are: The climate affects land transportation in the study area with different elements. It became clear through the study that rain is one of the most important climatic elements that greatly affects land transportation in the region. The study demonstrated the weakness of the necessary policies and funding on the part of the government regarding roads and bridges. Roads lose many citizens basic services such as education and health. The study demonstrated that land transport has a role in eliminating poverty by improving the population’s standard of living and increasing per capita income. The study recommends the following: the necessity of rehabilitating and maintaining roads and connecting the area with paved roads to the rest of the state, conducting studies and research related to the land transportation sector in the study area